Clinical observation of tubercular sellae meningioma and endo-suprasellar pituitary adenoma combination - Oleksandr Voznyak; Oleg Maydannyk; Andriy Litvinenko; Sergey Lysenko; V. Kropelnitskiy; G. Pasichnik (Ukrainian Neurosurgical Journal, 2012)
Сlinical observation of tubercular sellae meningioma and endo-suprasellar pituitary adenoma in 49 years old female patient, been verified at operation performing, is described. Clinical signs of the disease were analyzed, surgical treatment peculiarities, referred on total meningioma tubercular sellae  removing and endocapsular removing of pituitary adenoma are described. Combination of two different tumors was confirmed by data of histological analysis.At observation during 1 year after operation signs of tubercular sellae meningioma prolonged growth were no revealed also there was a negative dynamics of pituitary adenoma growth. Authors analyzed data from literature sources on a subject of the research, single observations of specified tumors combination were found.